Penerapan Model Pembelajaran Inkuiri Terbimbing Berbantuan Media Gambar Untuk Meningkatkan Hasil Belajar Kelas VIII SMPN 2 Nggoa - Serly Mura Ngguna; Vidriana Oktoviana Bano (Universitas Nusantara PGRI Kediri, 2023)
The background of this research is that there are still many students who are passive in the learning process and have an impact on the low learning outcomes of class VIII students at SMPN 2 Nggoa. The research objective is to improve student learning outcomes using guided inquiry learning models assisted by media images on the material of the human digestive system. This is a Classroom Action Research (CAR) designed by the Kemmis & Mc Tanggart model which consists of pre-cycle activities, cycle I and cycle II. The research subjects were 23 grade VIII students. Data collection techniques, namely tests, psychomotor assessment rubric and documentation. Data analysis techniques using quantitative descriptive. The results showed an increase in student learning outcomes was seen in the cognitive domain of pre-cycle of 13.04%, cycle I reached 43.47% and experienced an increase in cycle II to 82.60%. In the psychomotor aspect, 15 students (65.21%) with good predicate, 5 students (21.73%) with sufficient predicate and 3 students (13.04%) with poor predicate. It can be concluded that the application of the guided inquiry learning model assisted by media images can improve student learning outcomes in science subjects on the material of the human digestive system at SMPN Nggoa.